2020
DOI: 10.3762/bjnano.11.120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fluorination on interface energetics and growth of pentacene on Ag(111)

Abstract: We studied the structural and electronic properties of 2,3,9,10-tetrafluoropentacene (F4PEN) on Ag(111) via X-ray standing waves (XSW), low-energy electron diffraction (LEED) as well as ultraviolet and X-ray photoelectron spectroscopy (UPS and XPS). XSW revealed that the adsorption distances of F4PEN in (sub)monolayers on Ag(111) were 3.00 Å for carbon atoms and 3.05 Å for fluorine atoms. The F4PEN monolayer was essentially lying on Ag(111), and multilayers adopted π-stacking. Our study shed light not only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The authors argued that the weaker pushback effect and the unexpected ELA should be explained by a much larger adsorption distance of PFP compared to PEN [262]. Recently, direct XSW measurements have con rmed this [492]. Another interesting nding, which indicates a considerable interaction even within the physisorptive regime, was reported by Lo et al [491]: using STM it was found that PEN may change the surface reconstruction of Au(111) and thereby suggesting a stronger interaction with the substrate than PFP.…”
Section: Intermediate Casesmentioning
confidence: 97%
“…The authors argued that the weaker pushback effect and the unexpected ELA should be explained by a much larger adsorption distance of PFP compared to PEN [262]. Recently, direct XSW measurements have con rmed this [492]. Another interesting nding, which indicates a considerable interaction even within the physisorptive regime, was reported by Lo et al [491]: using STM it was found that PEN may change the surface reconstruction of Au(111) and thereby suggesting a stronger interaction with the substrate than PFP.…”
Section: Intermediate Casesmentioning
confidence: 97%
“…The authors argued that the weaker pushback effect and the unexpected ELA should be explained by a much larger adsorption distance of PFP compared to PEN 262 . Recently, direct XSW measurements have confirmed this 492 . Another interesting finding, which indicates a considerable interaction even within the physisorptive regime, was reported by Lo et al 491 : Using STM it was found that PEN may change the surface reconstruction of Au(111) and thereby suggesting a stronger interaction with the substrate than PFP.…”
Section: Fluorinationmentioning
confidence: 61%
“…Even if the decoupling is not fully achievedit is most effective when the graphene–substrate interactions are also weak , a graphene buffer layer does efficiently weaken the interface interactions. Similar effects have been reported for other 2D materials, such as hexagonal boron nitride, MoS 2 , and others. Such buffer layers can also modify the molecular orientation compared to the molecular orientation without a buffer layer. This change in orientation can be limited to the first adsorbed layer but also extended to further layers, ,, which in turn further influences the electronic properties of the molecular film. , …”
Section: Introductionmentioning
confidence: 99%
“…This change in orientation can be limited to the first adsorbed layer but also extended to further layers, 32,37,38 which in turn further influences the electronic properties of the molecular film. 19,37 This article is licensed under CC-BY 4 High-quality graphene can be grown on various transition metal surfaces by means of chemical vapor deposition, using primarily ethylene (C 2 H 4 ). As the precursor decomposition is typically limited once the catalytic metal surface is covered by a complete graphene layer, growth is easily limited to a monolayer.…”
Section: ■ Introductionmentioning
confidence: 99%